Enhanced invasion and survival of antibiotic- resistant Klebsiella pneumoniae pathotypes in host cells and strain-specific replication in blood - Klaper, Kathleen; Pfeifer, Yvonne; Heinrich, Lena; Prax, Marcel; Krut, Oleg; Bekeredjian-Ding, Isabelle; Wahl, Anika; Fischer, Martin A.; Kaspar, Heike; Borgmann, Stefan; Gerlach, Roman G.; Werner, Guido (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundKlebsiella pneumoniae is one of the most important opportunistic pathogens causing healthcare-associated and community-acquired infections worldwide. In recent years, the increase in antibiotic resistance and infections caused by hypervirulent K. pneumoniae poses great public health concerns. In this study, host-pathogen interactions of different K. pneumoniae strains of human and animal origins were analyzed in microbiological, cell-biological and immunological experiments.MethodsIn vitro infection experiments using representatives of different K. pneumoniae pathotypes and various epithelial and macrophage cell lines were executed analyzing adhesion, invasion and intracellular replication. Experimental conditions involved normoxia and hypoxia. Furthermore, survival and growth of further K. pneumoniae isolates expressing defined siderophores in blood (platelet concentrates, serum) was investigated. All experiments were done in triplicate and statistically significant differences were determined.ResultsSignificant differences in adhesion and invasion capability, phagocytosis resistance and intracellular replication were measured between different K. pneumoniae pathotypes. Especially, ESBL-producing K. pneumoniae isolates demonstrated increased invasion in host cell lines and survival in macrophages. A strong cytotoxic effect on intestinal cells was observed for hypervirulent K. pneumoniae. The results from our investigations of the growth behavior of K. pneumoniae in platelets and serum showed that siderophores and/or an enlarged capsule are not essential factors for the proliferation of (hypervirulent) K. pneumoniae strains in blood components.ConclusionOur in vitro experiments revealed new insights into the host-pathogen interactions of K. pneumoniae strains representing different pathovars and clonal lineages in different infectious contexts and hosts. While a clear limitation of our study is the limited strain set used for both infection and as potential host, the results are a further step for a better understanding of the pathogenicity of K. pneumoniae and its properties essential for different stages of colonization and infection. When developed further, these results may offer novel approaches for future therapeutics including novel “anti-virulence strategies”.